2021
DOI: 10.1016/s2352-3018(21)00048-5
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating oral PrEP into standard prevention services for South African women: a nested interrupted time-series study

Abstract: Background As oral pre-exposure prophylaxis (PrEP) becomes the standard of prevention globally, its potential effect on HIV incidence in clinical trials of new prevention interventions is unknown, particularly for trials among women. In a trial measuring HIV incidence in African women, oral PrEP was incorporated into the standard of prevention in the trial's last year. We assessed the effect of on-site access to PrEP on HIV incidence in this natural experiment.Methods We did a nested interrupted time-series st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
(33 reference statements)
1
15
0
Order By: Relevance
“…10 Furthermore, HIV incidence in ECHO dropped by about 50% after on-site access to PrEP. 20 We found that 40% of women discontinued PrEP before the final visit in our study, and this was consistent with findings from a large systematic review and meta-analysis where about a third discontinued PrEP within the first month. 21 In our study and the VOICE trial, older age was associated with quantifiable tenofovir.…”
Section: Discussionsupporting
confidence: 91%
“…10 Furthermore, HIV incidence in ECHO dropped by about 50% after on-site access to PrEP. 20 We found that 40% of women discontinued PrEP before the final visit in our study, and this was consistent with findings from a large systematic review and meta-analysis where about a third discontinued PrEP within the first month. 21 In our study and the VOICE trial, older age was associated with quantifiable tenofovir.…”
Section: Discussionsupporting
confidence: 91%
“…Since the costs of these interventions are not all derived from the same study, the methodology of determining the unit costs of the different interventions in different countries may not be comparable. Oral PrEP costs may go down as implementation efficiencies are identified, and its cost-effectiveness will also increase if, as was demonstrated in the SEARCH and other studies, 31 , 47 , 48 , 49 users correctly identify periods when they are at higher risk and use the intervention during these periods. 50 Despite these limitations, the overall trends identified in this study of three sub-Saharan African countries with different epidemic characteristics should be applicable to other sub-Saharan African countries with generalized HIV epidemics.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, HIV incidence in many PrEP implementation studies has been substantially lower than expected in the absence of PrEP despite a minority of participants adhering to PrEP. HIV incidence among all participants was 55% lower after PrEP became available during the Evidence for Contraceptive Options in HIV Outcomes (ECHO) trial in South Africa despite only 26% of participants reporting PrEP use [38]. In a study of young women in South Africa and Zimbabwe, only 21% of participants had high adherence (≥ 700 fmol/punch by dried blood spot) at 6 months after initiation.…”
Section: Discussionmentioning
confidence: 99%